The construction of grammar knowledge - Xavier Fontlich (Corela)
In this paper we present a natural classroom study on the construction of grammar knowledge. Pupils in their last year of compulsory education (ages from 15 to 16) in a bilingual context (Castilian/Spanish and Catalan in Barcelona) carry on a metalinguistic activity. Some results underline a contradictory situation: pupils refer to important grammar concepts although in a poor argumentative context. Further research should explore the links between a richer interaction and an effective development of grammar concepts in a more effective manner.